Associative information value of phonetic units in poetic discourse (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2015)
This article deals with sounds’ ability to generate semantic and pragmatic dominants as an element of the aesthetic reflection of objective reality phenomena in Ukrainian poetic language. The interpretation of associative information value of vocal and consonant units, as well as their distinctive features has implemented in the context of individual and national characteristics of world’s linguistic picture.
Keywords: Ukrainian poetic discourse; association; connotation; phonetic units; vowels; consonants